Tissue resident macrophages and their role in healthy and obese adipose tissues - Loo, Wan Yi (2019)
Adipose tissue macrophages (ATMs) present in the epididymal white adipose tissue (EWAT) are separated into three subpopulations expressing different levels of MHC class II as well as CD11c (F4/80hiCD11bintMHC class IIlowCD11c-, F4/80hiCD11bintMHC class II+CD11c- and F4/80hiCD11bintMHC class II+CD11c+). In this study, we show that in lean mice only two main subpopulations of ATMs are detectable, whereas in obese mice a massive infiltration of CD11c-expressing ATMs is infiltrating the adipose tissue. To investigate the contribution of ATM in adipose tissue physiology and pathology, we took advantage of a transgenic CD169-DTR mouse line where tissue resident macrophages can be ablated in vivo upon Diphteria toxin injection. After having confirmed the total lack all three ATM subsets by flow cytometry, we closely analysed the adipose tissue in terms of cellularity, size and numbers of adipocytes as well as presence of adipocyte-specific proteins, chemokines and pro-inflammatory cytokines. Clearly in absence of ATM, adipocytes not only change their size and become hypertrophic, but also their secretion profile is perturbed since adiponectin and leptin levels were almost undetectable in AT collected from DT-treated CD169-DTR mice. At the same time, in these mice higher levels of pro-inflammatory cytokines and chemokines are measured. This provides novel insights on the crucial contribution of ATM in controlling metabolic processes associated with obesity.